The Characteristics, Prognosis, and Risk Factors of Lymph Node Metastasis in Early Gastric Cancer - Xuan Li; Shiyu Liu; Jin Yan; Lei Peng; Meihong Chen; Jiajia Yang; Guoxin Zhang (Gastroenterology Research and Practice)
Background. Lymph node metastasis (LNM) is the most important risk factor for endoscopic treatment in early gastric cancer (EGC) patients. We aimed to investigate the rate of LNM, the risk factors, and the prognosis of EGC patients with LMN. Methods. A total of 10,039 patients who underwent gastrectomy with lymphadenectomy were reviewed between January 2010 and December 2015 at Jiangsu Province Hospital in China. Among them, we identified 1004 (10%) EGCs. First, endoscopic and clinicopathological features related to LNM were analyzed, and then risk factors for LNM were identified using univariate and multivariate analysis. Finally, the short- and long-term outcomes were compared between the groups. Results. LNM occurred in 123 (12.3%) EGCs. Most of EGCs were male (n=720, 71.7%) and mean age was 59.65 ± 11.09 years. The rate of H. pylori infection was 78.0% (783/1004). LNM was significantly associated with age, sex, location, lesion size, macroscopic type, depth of invasion, differentiation type, histological morphology, lymphovascular invasion (LVI), and TMN stage. By multivariate analysis, significant independent risk factors for LNM in EGC were identified as following: male sex (OR 2.365, P=0.035), age ≦ 40 (OR 0.055, P=0.012), depressed type (OR 2.721, P=0.013), submucosa invasion (OR 2.987, P=0.032), LVI (OR 5.186, P=0.003), tumor located in corpora (OR 8.904, P=0.047), and in angle (OR 12.998, P=0.024). 86.5% were successfully followed up for 3 years. The overall 1- and 3-year survival rates in LNM group were 100% and 91.1%, respectively, and those with no LNM were 100% and 100%, respectively. Conclusion. EGCs were investigated in 10.0% of gastric cancer, which LNM occurred in 12.3% of EGC. Independent risk factors of LNM included male sex, age (>40), the depth of invasion, LVI, and tumor located in corpora or angle. The 3-year overall survival rate was greater in EGC patients without LNM.